2015
DOI: 10.1037/a0039325
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Perceived Parental Autonomy Support Scale (P-PASS).

Abstract: Using a multidimensional perspective, the Perceived Parental Autonomy Support Scale (P-PASS) assesses autonomy-supportive and controlling parenting (Grolnick & Pomerantz, 2009). Two studies document the instrument's psychometric properties (Study 1, N ϭ 210, mean age ϭ 18.8 years; Study 2, N ϭ 315, mean age ϭ 18.5 years). Exploratory factor analyses first show that the P-PASS factor structure is best described by a 2-factor solution, 1 representing perceived autonomy support and the other, controlling parentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
195
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(214 citation statements)
references
References 58 publications
(105 reference statements)
10
195
2
7
Order By: Relevance
“…Reliability coefficients were high (a = .85 for autonomy support and a = .85 for controlling parenting). Past research shows that autonomy-supportive and controlling behaviors form two separate factors in exploratory factor analyses (Mageau et al 2015a). Also, higher-order factor analysis showed that the six subscales load in expected ways on two higher-order factors, with three subscales loading on an autonomy-supportive secondorder factor and three subscales loading on a controlling one (Fournier et al 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reliability coefficients were high (a = .85 for autonomy support and a = .85 for controlling parenting). Past research shows that autonomy-supportive and controlling behaviors form two separate factors in exploratory factor analyses (Mageau et al 2015a). Also, higher-order factor analysis showed that the six subscales load in expected ways on two higher-order factors, with three subscales loading on an autonomy-supportive secondorder factor and three subscales loading on a controlling one (Fournier et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents evaluated their mothers' use of autonomysupportive and controlling behaviors using the Perceived Parental Autonomy Support Scale (P-PASS; Mageau et al 2015a). The P-PASS measures three autonomy-supportive behaviors and three controlling practices using a 4-item subscale per behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, adolescents must perceive that their behaviors are determined by themselves or if not completely self-determined, at least supported by their parents. As the most important socializing agent in adolescents’ lives, parents may create an autonomy-supportive environment that promotes autonomous motivation or an autonomy-controlling environment that elicits amotivation (Mageau, Joussemet, Koestner, Moreau, & Forest, 2015), although research is scarce on the relationships between parenting practices and adolescents’ leisure motivations.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Moreau and Mageau (2012) developed the perceived autonomy support scale for employees (PASS-E). However, this scale is also an ad hoc scale based on the perceived parental autonomy support scale (Mageau et al, 2011), and it only measures employees' perceptions of their managers' autonomy support. No previous scale properly reflects the assumptions of SDT by including all three aspects of need support at work: autonomy, competence, and relatedness support.…”
Section: Existing Instruments and Their Limitationsmentioning
confidence: 99%